Different doses of atropine on heart rate fluctuations during reversal of neuromuscular blockade. - Islam, MA; Shahida, SM; Islam, MR; Haque, MM; Rashid, MH; Rashid, MH (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):595-9 The abstract of this article is available on the PubMed website